EFFECT OF MIXING ZNO:TIO2 NANOPARTICLES IN P3HT:PCBM SOLAR CELLS - Ali, S.; Zareen, A.; Ikram, M.; Murray, R.; Hussain, A.; Shah, S. Ismat (European Scientific Journal, ESJ, 2014)
In this study, we examine the effect of various ratios of TiO2 and ZnO nanoparticles in the active layer of organic solar cells (OSC). The organic polymers used in active layer are poly (3-hexylthiophene) (P3HT) and acceptor phenyl-C61-butyric acid methyl ester (PCBM). The active layer blend was prepared in chlorobenzene using various amount of metal oxides and PCBM, while keeping the constant ratio of P3HT. The power conversion efficiency (PCE) of the devices is found to decrease in presence of metal oxides in the blend of active layer of the devices. The PCE dropped from 1.43% to 1.29 %. The PCE decreased due to poor distribution of inorganic metal oxides in the active layer of the device, due to significant difference size of nano particles of the metal oxides. The mixing in active layer is found to decrease series resistance (Rs) of the devices and increasing fill factor (FF), but the Jsc is found to decrease probably due to increase in recombination current origionating from poor mixing of metal oxides in the active layer. The absorption and surface roughness increased with addition of the metal oxides in the active layer of the devices. The performances of the devices depend upon the optimun ratios of metal oxides with P3HT and PCBM.